A numerical study of particle deposition in ribbed duct flow with different rib shapes. (December 2015) - Lu, Hao; Lu, Lin
Abstract: The effects of surface rib shapes on particle deposition in turbulent duct air flows were numerically studied based on the Reynolds stresses model (RSM) with UDF code correction and the discrete particle model (DPM). The shapes of the rib cross sections were square, triangular and circular. The ratios of rib height to duct diameter e/D were 0.1. The present air velocity distributions for both smooth and ribbed ducts as well as particle deposition velocity in a smooth duct are all in good agreement with previous related study data. An efficiency ratio has been defined to evaluate the particle deposition enhancement ratio together with the increase of flow drag. It is found that the square ribs have the maximum enhancement efficiency on particle deposition, compared with the other rib shapes. The maximum efficiency ratio can reach about 400 for small particles ( τ p + < 1 ) but only about 2 for large particles ( τ p + > 1 ) when the rib shape is square. Moreover, the mechanisms of particle deposition enhancement for different rib shapes were investigated and analyzed. Highlights: The effects of rib shapes on particle deposition enhancement are investigated. The maximum particle deposition enhancement is obtained for square ribs. The mechanisms of particle deposition enhancement are analyzed and discussed. Pressure drop-weighted deposition enhancement is evaluated for different rib shapes.